Cyclin B Export to the Cytoplasm via the Nup62 Subcomplex and Subsequent Rapid Nuclear Import Are Required for the Initiation of Drosophila Male Meiosis. - Yamazoe, K.; Inoue, Y.H. (Cells, 2023)
The cyclin-dependent kinase 1 (Cdk1)-cyclin B (CycB) complex plays critical roles in cell-cycle regulation. Before Drosophila male meiosis, CycB is exported from the nucleus to the cytoplasm via the nuclear porin 62kD (Nup62) subcomplex of the nuclear pore complex. When this export is inhibited, Cdk1 is not activated, and meiosis does not initiate. We investigated the mechanism that controls the cellular localization and activation of Cdk1. Cdk1-CycB continuously shuttled into and out of the nucleus before meiosis. Overexpression of CycB, but not that of CycB with nuclear localization signal sequences, rescued reduced cytoplasmic CycB and inhibition of meiosis in Nup62-silenced cells. Full-scale Cdk1 activation occurred in the nucleus shortly after its rapid nuclear entry. Cdk1-dependent centrosome separation did not occur in Nup62-silenced cells, whereas Cdk1 interacted with Cdk-activating kinase and Twine/Cdc25C in the nuclei of Nup62-silenced cells, suggesting the involvement of another suppression mechanism. Silencing of roughex rescued Cdk1 inhibition and initiated meiosis. Nuclear export of Cdk1 ensured its escape from inhibition by a cyclin-dependent kinase inhibitor. The complex re-entered the nucleus via importin ? at the onset of meiosis. We propose a model regarding the dynamics and activation mechanism of Cdk1-CycB to initiate male meiosis.